University Students' Coping Strategies with Victimization of Dating Violence - Öztürk, Meral; Gökkaya, Veda Bilican (Fırat University, 2022)
This study aims to examine the reactions of university students toward victimization of dating violence and their coping strategies. The research was conducted with 475 students studying at Sivas Cumhuriyet University, Faculty of Letters. 174 male and 301 female students participated in the study. The participants' mean age was ±21. In the study based on a correlational model, a personal information form and a questionnaire prepared by the researchers were used. The chi-square test of independence was performed in the data analysis. According to the findings, the level of the participants' dating violence victimization was high, and the most common type of violence among them was psychological violence. Those who were exposed to violence in dating relationships did not think of continuing their relationship in the future. While male victims preferred to leave the place where they were at the time of violence, women performed the actions of "responding," "yelling," and "asking for help" more. Unlike female victims, male victims tended not to report the violence they had experienced. Men preferred to remain silent about their dating violence victimization due to the fear of being labeled.However, women preferred to remain silent about violence because they did not want their environment to hear about the violence they had experienced. Finally, while female students reported dating violence frequently to law enforcement agencies, males preferred to share it with their family and friends more frequently. In both groups, the rate of those who would apply to social services was low, while women thought of applying to these institutions more often than men.

Bu çalışma üniversite öğrencilerinin flört şiddeti mağduriyetlerine gösterdikleri tepkileri ve şiddetle mücadele stratejilerini incelemeyi amaçlamaktadır. Araştırma Sivas Cumhuriyet Üniversitesi Edebiyat Fakültesinde eğitim gören 475 öğrenciyle gerçekleştirilmiştir. Araştırmaya 174 erkek, 301 kadın öğrenci katılmıştır. Katılımcıların yaş ortalaması ±21’dir. Araştırmada ilişkisel tarama modeli kullanılmış olup anket formunda kişisel bilgi formu ile araştırmacıların hazırladığı anket soruları yer almıştır. Verilerin analizi Ki-Kare Bağımsızlık Testi ile yapılmıştır. Bulgulara göre katılımcıların flört şiddeti mağduru olma düzeyleri yüksektir. Mağdurlar en sık psikolojik şiddet eylemlerine maruz kalmaktadır. Flört ilişkilerinde şiddete maruz kalanlar ileride ilişkilerini devam ettirmeyi düşünmemektedir. Mağdur erkekler şiddet anında bulundukları yeri terk etmeyi tercih ederken; kadınlar daha çok “karşılık verme”, “bağırma” ve “yardım isteme” eylemlerini gerçekleştirmektedir. Yine mağdur erkekler çoğunlukla gördükleri şiddeti bildirmeme eğiliminde iken, kadınların şiddeti bildirme istekleri daha yüksektir. Erkekler etiketlenme korkusundan, kadınlar içinde bulundukları durumun çevrelerince duyulmasını istememelerinden dolayı şiddete sessiz kalmayı tercih etmektedir. Son olarak mağdur kadınlar yaşadıkları şiddet eylemini emniyet güçlerine bildireceklerini/bildirdiklerini söylerken erkekler daha sıklıkla aile ve arkadaş çevresini tercih etmektedir. Her iki grupta da sosyal hizmet kurumlarına başvuracağını söyleyenlerin oranı düşüktür ancak kadınların erkeklere kıyasla daha sık bu kurumlara gitmeyi düşündükleri görülmektedir.
ÜNİVERSİTE ÖĞRENCİLERİNİN FLÖRT ŞİDDETİ MAĞDURİYETLERİ İLE MÜCADELE STRATEJİLERİ